2002
DOI: 10.1074/jbc.m201608200
|View full text |Cite
|
Sign up to set email alerts
|

ATF-1 Mediates Protease-activated Receptor-1 but Not Receptor Tyrosine Kinase-induced DNA Synthesis in Vascular Smooth Muscle Cells

Abstract: Previously we have demonstrated that activation of p38 mitogen-activated protein kinase (MAPK) and induction of DNA synthesis in response to receptor tyrosine kinase (RTK) and G protein-coupled receptor (GPCR) agonists require NADH/NADPH-like oxidase activity in vascular smooth muscle cells (VSMC). Here we tested the role of p38 MAPK in RTK and GPCR agonistinduced DNA synthesis in VSMC. Platelet-derived growth factor (PDGF)-BB and thrombin (RTK and GPCR agonists, respectively) activated p38 MAPK in a time-depe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
14
0

Year Published

2003
2003
2023
2023

Publication Types

Select...
8

Relationship

4
4

Authors

Journals

citations
Cited by 18 publications
(14 citation statements)
references
References 46 publications
0
14
0
Order By: Relevance
“…A role for iPLA 2 in lymphocyte growth has also been reported (31). Previously, we showed that p38 MAPK plays a role in thrombin-induced VSMC growth via activation of ATF-1 (36). Recently it was demonstrated that iPLA 2 plays a role in double stranded-RNA-induced nitric oxide synthase gene expression via activation of CREB (42).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…A role for iPLA 2 in lymphocyte growth has also been reported (31). Previously, we showed that p38 MAPK plays a role in thrombin-induced VSMC growth via activation of ATF-1 (36). Recently it was demonstrated that iPLA 2 plays a role in double stranded-RNA-induced nitric oxide synthase gene expression via activation of CREB (42).…”
Section: Resultsmentioning
confidence: 99%
“…Recently, we have reported that p38 MAPK via phosphorylation and activation of ATF-1 is involved in thrombin-induced growth in VSMC (36). Therefore, to understand the possible mechanism(s) by which thrombin stimulates iPLA 2 activity in VSMC, the role of p38 MAPK was FIG.…”
Section: Resultsmentioning
confidence: 99%
“…GPCRs, primarily through their cognate G proteins, regulate these three-tier MAPK phospho-relay systems to modulate the expression of specific primary as well as secondary response genes involved in cell proliferation, differentiation and apoptosis (Gutkind, 2000;Kranenburg and Moolenaar, 2001;Werry et al, 2005). G proteins have been shown to regulate diverse transcription factors such as AP-1 (Araki et al, 1997), NF-kB, CRE, SRE (Takeuchi and Fukunaga, 2003), ATF1 (Ghosh et al, 2002), STAT3 (Sellers et al, 1999), ELK1 (Todisco et al, 1997), Egr-1 (Gerasimovskaya et al, 2002), HIF-1a (Sodhi et al, 2000), MEF2 (Fukuhara et al, 2000a, b) via ERK-, JNK-, p38MAPKs-or ERK5 modules. However, only recently the dynamic and multilayered mechanisms by which G proteins regulate these MAPK networks have begun to be unraveled.…”
Section: Introductionmentioning
confidence: 99%
“…Because thrombin is produced at the sites of vascular injury and influences both migration and proliferation of VSMC (20,36), it is implicated in the pathogenesis of vessel wall diseases (14). In addition, the mechanism(s) by which thrombin influences its nonthrombotic actions, particularly the mitogenic effects in VSMC, is fairly well studied (4,30,33,26,31,29,16). Like many other G protein-coupled receptor (GPCR) agonists, thrombin, in addition to activation of its cognate protease-activated receptors, stimulates a number of signaling events in mediating its nonthrombotic effects.…”
mentioning
confidence: 99%